Gulf Stream variability in the context of quasi‐decadal and multidecadal Atlantic climate variability - McCarthy, Gerard D.; Joyce, Terrence M.; Josey, Simon A. (Geophysical Research Letters, 2018)
© The Author(s), 2018. This article is distributed under the terms of the Creative Commons Attribution License. The definitive version was published in Geophysical Research Letters 45 (2018): 11,257-11,264, doi:10.1029/2018GL079336. The Gulf Stream plays an important role in North Atlantic climate variability on a range of timescales. The North Atlantic is notable for large decadal variability in sea surface temperatures (SST). Whether this variability is driven by atmospheric or oceanic influences is a disputed point. Long time series of atmospheric and ocean variables, in particular long time series of Gulf Stream position, reveal differing sources of SST variability on quasi‐decadal and multidecadal timescales. On quasi‐decadal timescales, an oscillatory signal identified in the North Atlantic Oscillation (NAO) controls SST evolution directly via air‐sea heat fluxes. However, on multidecadal timescales, this relationship between the NAO and SST changes, while the relationship between the NAO and Gulf Stream position remains consistent in phase and resonant in amplitude. Recent changes in the Gulf Stream Extension show a weakening and broadening of the current, consistent with increased instability. We consider these changes in the context of a weakening Atlantic overturning circulation. European Commission (EC) Grant Number: 727852